Investigating EFL learners’ readiness of using smartphone and problems for learning oral English communication skills at tertiary level in an EFL context - Ibna Seraj, Prodhan Mahbub (International Association of Online Engineering, 2020)
Although extensive research has been carried out to investigate EFL learners' readiness of using smartphone and problems in global EFL contexts, there remains a scarcity of evidence on EFL learners' readiness of using smartphone and problems faced for learning oral English communication skills at tertiary level in Bangladesh. The present study was conducted to explore Bangladeshi tertiary level learners' readiness of using smartphone and problems for learning oral English communication skills. This study employed a mixedmethod design, using a survey questionnaire and semi-structured interview as data collection instruments. The participants of this study were sixty-one learners (35 females and 26 males) who were studying at the department of English of a university. The findings from the questionnaire illustrated that EFL learners' level of readiness of using a smartphone was high, and the frequent problems they faced were lack of authentic materials, audio-video aids, oral practice environment, large size class and existing teaching method. Subsequently, from the findings of semi-structured interview solicited three themes regarding EFL learners' readiness were availability, usability and positivity for the use of smartphone and four themes regarding EFL learners' problems, such as psychological, linguistic, teachers' efficacy and use of mother tongue for learning oral English communication skills.